Skeletal Metastasis as Detected by 18F-FDG PET with Negative CT of the PET/CT: Frequency and Impact on Cancer Staging and/or Management - Ahmed, Fatma; Muzaffar, Razi; Fernandes, Hermina; Tu, Yifan; Albalooshi, Batool; Osman, Medhat M. (Frontiers in Oncology, 2016)
Objectives: The aim of our study is to assess the frequency of detection of PET positive CT negative skeletal metastases (SM) and determine the impact of such detection on staging and/or management in patients who had FDG PET/CT as part of the cancer work up. Methods: We retrospectively reviewed 2000 18F-FDG PET/CT scans of known cancer patients. A log was kept to record cases of suspected SM with or without bone changes from the low-dose non-contrast CT. The presence or absence of SM was evaluated based on available pathological and clinical data. The impact of detection of such lesions on cancer staging and/or management was evaluated by a board certified oncologist. Results: Of the 2000 cases, 18F-FDG PET/CT suggested SM in 146/2000 (7.3%). Of those 146 cases, 105 (72%) were positive on both PET and CT. The remaining 41 (28%) had PET positive CT negative bone lesions. SM was confirmed in 36/41 (88%) PET positive/CT negative cases. This was based on biopsy, imaging or clinical follow-up. The detection of PET positive CT negative SM did not change staging or management in 7/36 (19.4%). However, staging and/or management was affected in 29/36 (80.6%). Conclusions: SM is not uncommon in 18F-FDG PET/CT, as it accounts for 146/2000 (7.3%) of cases. PET demonstrated FDG-avid SM without a CT abnormality in at least 36/146 (25%). Patients staging and or management changed in 29/36 (80.5%). We concluded that 18F-FDG PET is sensitive in detection of SM with significant impact on staging & or management. Key words 18F-FDG PET/CT, Skeletal metastasis, PET positive, CT negative